Some Emerging Nepali Abstract Painters of 1980s (SIRJANĀ – A Journal Of Arts and Art Education, 2023)
Nepali artists of 1980s further developed the subjective, abstract and plural art trends with their individual identity in the paintings. The movement was from objective representation to subjective expression; concrete reality to abstract concept; from external world to the inner experience; and from visible appearance to the invisible existence. Some representative artists of this period are Kiran Manandhar, Sharad Ranjit, Navindra Man Rajbhandari, and Jeevan Rajopadhyay. Mananandhar's paintings emphasize the inner expression through altered art forms. Sharad Ranjit presents the dancing colors suggesting the implied rhythm of the universe. Rajbhandari's artworks present the quest of light in the darkness and rhythmic melody in the silence. Jeevan Rajopadhyay's colorful compositions stand for themselves with the focus on the aesthetic pleasure of the colors and abstract shapes. Creative works of these artists attempt to capture the invisible and intangible aspects of reality in the aesthetic visual form. There is the curiosity to know the unknown – to see the unseen. The visual forms attempt to present this side of the reality through lines, rhythmic curves, unusual shapes, strange colors, and novel images. Since the visual forms are plural and open-ended, there is the possibility of multiple interpretations. Thus, this research is qualitative.